Species and distribution of inorganic selenium in the Bohai Sea - 姚庆祯 张经 (Chinese journal of oceanology and limnology, 2006)
For studying geochemical behavior of selenium, a marine investigation was conducted in September 1998 cruise in the Bohai Sea. Horizontal and vertical distributions of inorganic selenium and selenite were studied. The inorganic selenium varied from 0.73 to 2.41 nmol/L, with an average of 1.31 nmol/L; while selenite varied from 0.18 to 0.72 nmol/L with an average of 0.47 nmol/L. The average ratio of selenite to selenate was 0.68, and selenate was the predominant species of inorganic selenium in the most study area. Concentrations of inorganic selenium and selenite decreased with distance from the coast. No apparent variations of the concentration between surface and bottom was shown. There were two wa- ter masses in the area, one from the Huanghe （Yellow） River and other from the Yellow Sea. Of the two, Huanghe River was the major source of inorganic selenium.